2015
DOI: 10.1177/2325967115s00044
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Micronized Allograft Articular Cartilage (BioCartilage) and Platelet Rich Plasma to Augment Marrow Stimulation in an Equine Model of Articular Cartilage Defects

Abstract: Objectives:Microfracture continues to be a dominant treatment strategy for symptomatic articular cartilage defects. Improving the histologic and clinical outcomes with biologic adjuncts offers promise to enhance this widely utilized technique. Specifically, the use of a novel scaffold that is potentially conductive and inductive such as micronized allograft articular cartilage (BioCartilage-BC) combined with platelet rich plasma (PRP) was investigated as an adjunct to microfracture in an equine model of articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies in humans reported more hyaline-like tissue compared to microfracture alone (Abrams et al, 2013). In a recent equine study comparing BioCartilage to microfracture alone, better repair-host integration, base integration and collagen type II 13 months postoperatively were observed in chondral defects treated with BioCartilage compared to microfracture alone (Cole et al, 2015).…”
Section: Particulated Cartilage Graftsmentioning
confidence: 99%
“…Studies in humans reported more hyaline-like tissue compared to microfracture alone (Abrams et al, 2013). In a recent equine study comparing BioCartilage to microfracture alone, better repair-host integration, base integration and collagen type II 13 months postoperatively were observed in chondral defects treated with BioCartilage compared to microfracture alone (Cole et al, 2015).…”
Section: Particulated Cartilage Graftsmentioning
confidence: 99%